Study on Benchmarking Evaluation System for Technological Innovation of Power Grid Enterprises. Issue 2 (July 2020) - Chang, Yan; Meng, Weixuan
Abstract: China attaches great importance to corporate scientific and technological innovation, and technological innovation has become a powerful driving force for continuous promotion of corporate scientific development. According to the new requirements of the 19th National Congress of the Communist Party of China on the reform and development of central enterprises and the high-quality economic development of the Fourth Plenary Session of the 19th Central Committee, the company's scientific and technological innovation index evaluation was carried out. Based on the theoretical research, evaluation methods and enterprise management practices of world-class enterprises, this article establishes an effective mechanism to guide the technological innovation of power grid enterprises and provides a scientific decision-making basis for technological innovation of power grid enterprises.